Studi Kasus : Perubahan Tingkat Nyeri Pasien Nyeri Akut Post Op Sectio Caesarea Setelah Diberikan Progressive Muscle Relaxation - Aurelia Aidin, Anggi Desita; Puspitasari, R.A. Helda (Pusat Riset dan Inovasi Nasional, 2025)
Introduction : Sectio caesarea is a method of labor with abdominal and uterine surgical procedures. The prevalence of sectio caesarea at dr. R. Soedarsono Hospital was recorded at 83 cases in the first quarter of 2025. This action causes a break in tissue continuity that triggers the release of biochemical mediators and the transmission of pain impulses to the brain, resulting in acute pain nursing problems. One of the non pharmacological interventions to reduce pain levels is progressive muscle relaxation. Methods : This research is in the form of a case study with a nursing care approach for 3 days conducted on one post op sectio caesarea patient with acute pain nursing problems by providing interventions in the form of progressive muscle relaxation. Results : After 3 days of nursing care, the nursing problem of acute pain was resolved with a decrease in pain scale from 7 to 3. Discussion : Progressive muscle relaxation is proven effective in reducing pain levels in post op sectio caesarea patients.